Measurements of horizontal motion of the station Simeiz using VLBI - Petrov, L.Yu.; Voivach, O.E.; Nesterov, N.S. (Кинематика и физика небесных тел, 2001)
Estimates of the horizontal velocity of the radioastronomical station Simeiz were obtained using VLSI observations made under geodynamics programs during the years 1994—2000. The complete set of 3 million VLBI observations was analyzed, and it was found that the station moves with respect to the Eurasian tectonic plate, considered as rigid, with a rate of 2.8±0.9 mm/yr in the north-east direction. Possible local systematic effects were thoroughly studied and the reliability of the estimate of uncertainly of the results was evaluated. We investigated stability of the station with respect to local marks and revealed that an inclination of the azimuthal axis of the telescope increases with velocity 2.6". The estimate of vertical motion of the station, 2.6±3.0 mm/yr, is not statistically significant. Оцінки горизонтальної швидкості радіоастрономічної станції Сімеїз були отримані з використанням РНДБ-спостережень в рамках геодинамічних програм у 1994—2000 рр. 3 аналізу повної вибірки з З млн РНДБ-спостережень знайдено, що станція переміщується, відносно Євразійської тектонічної плити, яка вважається жорсткою, зі швидкістю 2.8±0.9 мм/рік у північно-східному напрямку. Були повністю вивчені можливі локальні систематичні ефекти і оцінена надійність результатів. Ми дослідили стабільність станції відносно локальних міток і показали, что нахил азимутальної осі телескопа збільшується зі швидкістю 2.6". Оцінка вертикального руху станції 2.6±3.0 мм/рік статистично незначима. VLBI is possible only as a result of the coordinated efforts of many people. The authors would to like to thank D. Ivanov, A. Ipatov and S. Mardyshkin for maintenance of the receivers at the station, M. Sorgente for his efforts in correlation as well as the personnel at 126 other VLBI stations, correlators and analysis centers. We are grateful to L. I. Matveenko for useful discussions that resulted in improving this paper.